"We See the World Different Now": Remapping Assumptions About International Student Adaptation. (February 2021) - Bittencourt, Tiago; Johnstone, Christopher; Adjei, Millicent; Seithers, Laura
Student mobility has become a key feature in the drive toward internationalization of higher education in the United States. International students contribute to the academic culture of universities, yet, often face isolation, discrimination, and experience difficulties transitioning to new environments. As a result, conational networks have formed to provide support to international students in foreign institutions. This article examines the different ways membership in a conational support group mediated international students' experiences in a university campus. Contrary to theories that suggest insularity such as fortressing and cultural enclaves, our findings suggest that conational groups are sites of creative potential where group members are consistently forging complex assemblages between norms that are familiar and experiences that are new. Although significant personal transformations ensue as a result of these assemblages, they are occurring in a setting and a pace that is determined by group members and perceived to be safe. We argue that conational groups should not be conceived as static spaces that reproduce cultural norms, but rather as sites of contestation and cultural negotiation. Based on these findings, we question whether "integration" should be a guiding institutional logic for international student engagement, suggesting instead an approach based on the concept of "inclusion."